Políticas de turismo e comunidade local no litoral potiguar - Taveira, Marcelo da Silva (2008)
This research focuses on raise the discussion of existance tourism policies in Rio Grande do Norte and its contributions to the integration of local communities in the coastal tourist activity. Guided by the background of the neoliberalism and its influence on the model of tourism development adopted in Rio Grande do Norte. For that, were surveyed the concrete realities of coastal localities of the municipalities of Ceará-Mirim, Extremoz, Parnamirim and Nísia Floresta covered by Prodetur-RN I and II, by being part of the tourist portion of the state that have received domestic and international investment and, because are located in the geographical area of the Potiguar capital, Natal. We interviewed the municipal managers and the residents of local communities who live in municipalities more than ten years. Also, was raised a discussion on the role of the state as the main agent of public policies and hegemonic facilitator in the attraction of domestic and foreign investments, with the main scenario the neoliberal model of economic development. Here discuss ways and strategies of socio-political organization of local communities, with regard to the inclusion in the tourist and, pointing to the critical development model in question and signaling other concepts of development model, such as local basis, for example. By the ending of the research, was concluded that the model of development of the tourism in the Rio Grande do Norte is reflected of the way of life of the society, that the communities live in precarious conditions and that the way of inclusion in the tourism is almost incipient. Also, it was possible to detect the inexistence of public politics of tourism that promoted the planning of the tourist activity, as well as, the inclusion of the communities in the decision processes and that, searched the development on the basis of the principles of sustainable and local autonomy